Adaptive Facilities for Supporting Differently-abled Persons in the Library Environment: A Case Study of Libraries in Shillong, Meghalaya, India - Laloo, Bikika; Kharmyndai, Learner (Journal of Information and Knowledge, 2015)
The differently-abled are emerging as a force that cannot be ignored today. While the capabilities of many of these are almost at par with and sometimes even surpass those of the 'abled', their special needs cannot also be denied. Public institutions of all kinds have geared up or are in the process of gearing up to facilitate the smooth movement and functioning of this group, with a variety of facilities, from general ones such as crutches, elevators, ramps, braille, hearing aids etc. to more specialized ones such as CUPID, Dexter etc. Libraries worldwide have also put many of these adaptive facilities in place. This study set out to explore whether libraries in Shillong, North East India, provide adaptive facilities for supporting the differently-abled. The study found that the libraries in Shillong are grossly under-equipped in this regard and that excuses abound. Reasons for not having adaptive facilities for the differently-abled range from lack of funds to 'absence of differently-abled patrons'- a claim that exposes the lack of planning on the part of the libraries. It was found however, that some Library staff members do realize the significance of the differently-abled and the need for facilitating their functioning in the Library environment.